치과위생사의 심리적 임파워먼트 및 리더-구성원 간 교환관계(LMX)와 직무 만족도의 관련성 - 윤나나; Na-na Yoon; 이지영; Ji-young Lee; 유병철; Byeng-chul Yu (Han'guk Ch'iwisaeng Hakhoe chi, 2017)
Objectives:This study aimed to identify the influences of leader-member exchange (LMX) and psychological empowerment of the dental hygienists on their job satisfaction. Methods: A self-administrated questionnaire survey was conducted from July 7 to August 2014 targeting 196 dental hygienists in Busan and Gyeongsangnam-do. Leader-member relationship, psychological empowerment and job satisfaction were evaluated by LMX scale, psychological empowerment scale and job descriptive index (JDI), respectively. Data were analyzed by descriptive analysis, t-test, one-way ANOVA, and multiple Linear regression analysis. Results: Overall LMX, psychological empowerment on job satisfaction level of subjects were 3.43±0.61, 3.38±0.66 and 3.20±0.42, respectively. The influential factors of LMX, psychological empowerment and job satisfaction were professional respect (subcategory of LMX), affect (subcategory of LMX), meaning (subcategory of psychological empowerment) and impact (subcategory of psychological empowerment). Conclusions: Job satisfaction of dental hygienist is closely related to professional respect, affect, meaning and impact.